Agreement Between Self-Report and Medical Record Prevalence of 16 Chronic Conditions in the Alaska EARTH Study - Kathryn R. Koller; Amy S. Wilson; Elvin D. Asay; Jesse S. Metzger; Diane E. Neal (SAGE Publishing, 2014)
The gold standard for health information is the health record. Hospitalization and outpatient diagnoses provide health systems with data on which to project health costs and plan programmatic changes. Although health record information may be reliable and perceived as accurate, it may not include population-specific information and may exclude care provided outside a specific health care facility. Sole reliance on medical record information may lead to underutilization of health care services and inadequate assessment of population health status. In this study, we analyzed agreement, without assuming a gold standard, between self-reported and recorded chronic conditions in an American Indian/Alaska Native cohort. Self-reported health history was collected from 3821 adult participants of the Alaska EARTH study during 2004-2006. Participant medical records were electronically accessed and reviewed. Self-reported chronic conditions were underreported in relation to the medical record and both information sources reported the absence more reliably than the presence of conditions (across conditions, median positive predictive value = 64%, median negative predictive value = 94%). Agreement was affected by age, gender, and education. Differences between participant- and provider-based prevalence of chronic conditions demonstrate why health care administrators and policy makers should not rely exclusively on medical record-based administrative data for a comprehensive evaluation of population health.